Properties of ethylene-vinyl acetate filled with metal hydroxide - Sabet, Maziyar (SAGE Publications Ltd., 2015)
In this study, the properties of ethylene-vinyl acetate (EVA) and EVA filled with aluminum (aluminum trihydrate; ATH) and magnesium hydroxide (MH) as halogen-free flame-retardant materials were studied. Scanning electron microscopic analysis revealed that MH in EVA matrix is platy in structure, considerably broad size distribution and well homogeneously distributed, whereas ATH particles are smaller and much more homogeneous in size. Addition of ATH or MH to EVA had an impressive affection on the thermal aging and flame tests but impaired the blend mechanical properties. This research explored that in comparison with ATH, addition of MH to EVA blends was more efficient and suitable in all mechanical, thermal, and flammability tests.